2007
DOI: 10.4102/jsava.v78i2.293
|View full text |Cite
|
Sign up to set email alerts
|

Some fungi, zearalenone and other mycotoxins in chicken rations, stock feedstuffs, lucerne and pasture grasses in the communal farming area of Rhenosterkop in South Africa

Abstract: Mycotoxins may be present in feeds without any visible signs of mould contamination. There is a need for rapid and accurate measurement of mycotoxins for purposes of continual monitoring and identification of high risk commodities. Samples from commercial chicken feed (maize kernels), cattle feed (lucerne, grass and hay) and milk were analysed for the presence of certain mycotoxins and cultured for fungi. Results of fungal profiles showed that most samples were contaminated by moulds belonging to the genera, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The presence of potential AF producer strains and AFB 1 in commercial poultry feeds has been extensively reported in previous studies (Dalcero et al, 1997(Dalcero et al, , 1998Oliveira et al, 2006;Fraga et al, 2007;Naicker et al, 2007;Zinedine et al, 2007). However, the aim of producers, researchers, and governments is to develop effective prevention management and decontamination technologies to minimize the toxic effects of AF in animal production.…”
Section: Introductionmentioning
confidence: 88%
“…The presence of potential AF producer strains and AFB 1 in commercial poultry feeds has been extensively reported in previous studies (Dalcero et al, 1997(Dalcero et al, , 1998Oliveira et al, 2006;Fraga et al, 2007;Naicker et al, 2007;Zinedine et al, 2007). However, the aim of producers, researchers, and governments is to develop effective prevention management and decontamination technologies to minimize the toxic effects of AF in animal production.…”
Section: Introductionmentioning
confidence: 88%
“…maize (Rava et al 1996). As levels in dairy feed are regulated, levels currently found in feeds are generally below this limit (Naiker et al 2007), but if farmers produce their own commodities and feed, this may exceed the limit at various times due to lack of strict quality control. Inevitably this will lead to AFM1 in the milk of animals fed contaminated feed, which is the case in Kenya (Kang'ethe and Lang'a 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Apart from aflatoxins, fumonisins, deoxynivalenol and ochratoxin A, which are regarded as important mycotoxins, based on their worldwide occurrences and intoxication (Ayalew et al, 2006;Naicker et al, 2007), zearalenone is also amongst the important mycotoxins implicated in contamination of sorghum grains. Furthermore, it has been reported that Fusarium isolates from bananas can also produce zearalenone (Jiménez et al, 1997).…”
Section: Zearalenone (Zea)mentioning
confidence: 99%